Characterizing p-wave velocity and elastic properties of sedimentary rocks for foundation of building / Nurul Huda Abdullah...[et al.] - Abdullah, Nurul Huda; Sazaly, Nur Nabila; Awang, Haryati; Hamid, N.H. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The aim of this paper is to develop empirical models based on laboratory experimental works using a number of rock samples using seismic velocity parameters and deformation properties. Furthermore, it is very important to express the relationship between elastic properties and seismic velocity of tropical sedimentary rocks which can be used for construction of foundation building. Ultrasonic pulse velocity test (UPV) is used worldwide to measure ultrasonic wave velocity which able to penetrate through intact rock and the wave travel time is depending on the particle arrangement of rock microstructure. Elastic properties of rock such as Young modulus, shear modulus and bulk modulus can be determined by conducting uniaxial compressive strength test (UCS) with deformation measurement. The results between the P-wave velocity were correlated and regression equations were established to present the correlation between them. Regression analysis (R2) shows that the correlation values of P-wave and Young modulus, shear modulus and bulk modulus at 0.63, 0.61 and 0.60, respectively. It can be concluded that from the relationship of P-wave and elastic properties parameters, the result of allowable soil bearing pressure can be used for design foundation building and the laboratory analysis of samples is used to predict P-wave velocity.